TECHNICAL SUPPORT POLICY OF THE ARMED FORCES OF THE REPUBLIC OF UZBEKISTAN - Gulirano Abduganiyeva (Western European Studies, 2025)
This article analyzes the results achieved by the Republic of Uzbekistan in providing its national army with modern military equipment and weaponry over the past thirty years. The study examines the reforms undertaken by Uzbekistan in this field, taking into account the achievements of foreign countries, the economic potential of the republic, its geostrategic position, ongoing regional processes, and other significant factors
Keywords: armored vehicles; unmanned aerial vehicles; anti-aircraft missile systems